Oxford story tree: lost in the jungle - Hunt, Roderick; Lui, Linda Brychta, Alex (Oxford University Press HongKong, 2014)
"Lost in the Jungle" by Roderick Hunt is a children's story featuring the familiar characters from the Oxford Reading Tree series, particularly Biff, Chip, and Kipper. In this adventure, the children find themselves in a jungle environment, where they encounter various animals and challenges. As they navigate through the jungle, they learn important lessons about teamwork, bravery, and problem-solving. The story combines excitement and exploration, making it engaging for young readers while also emphasizing themes of friendship and adventure.